Pillar capitals and rotunda, Frere temple - Ghosh, Ayan (2023)
Frere Temple is made from Porbandar stone. The circular rotunda is supported by six pillars of the Corinthian order, their capitals decorated with acanthus leaves and scrolls. However, unlike Corinthian pillars that are almost always fluted, the pillars at the Frere temple are not fluted.